ANALYSIS OF THE ROLE OF LEARNING MOTIVATION IN MODERATING THE INFLUENCE OF SELF-EFFICACY AND SELF-REGULATED LEARNING ON ACCOUNTING COMPUTER LEARNING OUTCOMES - Saputri, Anggun; Muliasari, Indah; Mardi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this research to know and analyze the role of learning motivation in moderating the influence of self-efficacy and self-regulated learning on accounting computer learning outcome. Affordable population in this research amounted to 142 students of class XI financial accounting and institution at SMK Negeri 50 & 46 Jakarta. This research using quantitative research with survey method. Data collection using questionnaires and documentation. Data processing using application of SPSS v.25 with moderated regression analysis (MRA) model. The result of this research show that self-regulated learning has a positive and significant influence on accounting computer learning outcome. But, self-efficacy has no significant influence on accounting computer learning outcome. So, learning motivation can’t moderate the influence of self-efficacy on accounting computer learning outcome. However, learning motivation can moderate the influence of self-regulated learning on accounting computer learning outcome. Thus, the role of learning motivation in moderating the influence of self-efficacy and self-regulated learning can be the right choice for teachers to develop student learning outcome in accounting computer learning.